Biocatalytic and bioelectrolytic decolorization of simulated melanoidin wastewaters by Saccharomyces cerevisiae cells suspended and conjugated on silica and alumina. Issue 5 (October 2020) - Tsiakiri, E.P.; Sompatzi, E.; Voukia, F.; Sotiropoulos, S.; Pantazaki, A.A.
Graphical abstract: Highlights: Bakery yeast cells were covalently-immobilized on alumina/silica particles. Melanoidin degradation obtained after 48 h reached a rate 80% and 100% for alumina and silica supports. Secretion of laccase and peroxidase activity participate in melanoidin decolorizartion. Bioelectrolytic melanoidin oxidation catalyzed both by laccase and yeast cells at a graphite electrode (GR). A melanoidin decolorization of 70% was achieved after 6 h of bioelectrolysis at a final current value 12 μΑ. Abstract: Melanoidins are brown compounds resistant to degradation. Bakery yeast S. cerevisiae cells were covalently-immobilized on alumina and silica particles for melanoidin degradation reaching a rate of 80% and 100% after 48 h respectively. Degradation is due to secretion of laccase and peroxidase activity stimulated by Cu 2+ and Mn 2+ .The bioelectrolytic melanoidin oxidation catalyzed both by laccase and yeast cells at a graphite electrode (GR). The electrochemical cell studied by cyclic voltammetry. A chronoamperometric curve recorded by application of a constant electrolysis potential of +1.10 V at a GR electrode within a reaction solution containing 2, 2′-azinobis-(3-ethylbenzothiazoline-6-sulfonic acid (ABTS), melanoidin and the biocatalyst, for a period of 6 h. A decolorization of 70% was achieved after 6 h of bioelectrolysis at a final current value 12 μA. The kinetic data of heterogeneous catalysis for the immobilized yeasts, were compared with those of the electrode (GR), obtaining a kinetic value khet of 5.81 * 10 −5 m/s.